The Author’s Mastery In Creating Humorous Images - Ramazonova Nafisa Ixtiyor qizi (International Journal Of Literature And Languages, 2025)
This study explores the use of humor and humorous imagery in Miss Billy by Eleanor H. Porter. It examines how Porter employs comedic elements, character contrast, and social-domestic settings to enrich the narrative, convey moral values, and shape the reader’s emotional engagement. The analysis highlights the novel’s strengths—its vivid characterizations, effective humor, and representation of social class—while also noting potential weaknesses, such as the protagonist’s inconsistent emotional decisions.